Efficacy of intradermal injection of tranexamic acid and ascorbic acid versus tranexamic acid and placebo in the treatment of melasma: A split‐face comparative trial. Issue 2 (9th March 2022) - Pazyar, Nader; Molavi, Seyedeh Nasrin; Hosseinpour, Parisa; Hadibarhaghtalab, Maryam; Parvar, Seyedeh Yasamin; Dezfuly, Motahareh Babazadeh
Abstract: Background and Aims: Melasma is a common dermatologic disorder characterized by symmetrical hyperpigmented lesions on the face. Although various therapeutic options are available for melasma, its treatment remains challenging. The present study evaluated the safety and efficacy of intradermal microinjection of tranexamic acid (TA) plus ascorbic acid in treating melasma lesions compared with TA and placebo. Methods: From September 2019 to May 2020, 24 patients with symmetrical melasma were enrolled in a prospective, double‐blind, split‐face, randomized controlled clinical trial. Each patient received 50 mg/ml TA and 50 mg/ml ascorbic acid for one side of the face (A) and 50 mg/ml TA and placebo for the other side (B) every 2 weeks for 12 weeks. The Melasma Area and Severity Index (MASI) score, Physician Global Assessment, and pain were measured at baseline and at 4, 8, 12, and 24 weeks. Statistical analysis was done using SPSS software version 16, and data were reported as mean ± standard deviation or median and interquartile range. χ 2 and Fisher's exact tests were used to test differences between the groups. Results: Both groups experienced a significant decrease in MASI scores compared with the baseline. The MASI score was significantly less in the intervention group than the placebo group at the 8th and 12th weeks. However, burning pain was significantly more prominent in the intervention group. Conclusion: Intradermal injection of ascorbic acid combined with TA can be beneficial in treating melasma. Currently, there are numerous treatment modalities for melasma. However, the results still vary, and satisfactory outcomes are yet to be reached.